TRANSFORMATION OF BUREAUCRATIC DIGITAL SERVICES THROUGH THE SALAMAN APPLICATION AT THE BANDUNG CITY POPULATION AND CIVIL REGISTRATION OFFICE - Sukrisno Sukrisno (Jurnal Ilmiah Wahana Bhakti Praja, 2023)
E-Government is a prominent focal point that aims to foster governmental innovation in the realm of public services. This was achieved through web browsers or easily downloadable smartphone applications, especially due to the Covid-19 pandemic. Within the Bandung City Population and Civil Registration Office, the implementation was a significant initiative in delivering services to the public. In addition, this was facilitated by the SALAMAN (SelesAi daLAm genggaMAN) Application, initially launched in December 2018. Meanwhile, the transition towards digital bureaucratic services in public administration was observed as a shift from traditional office-based administrative functions, embracing an improved paradigm by harnessing information technology. Therefore, this research aimed to evaluate the effectiveness and efficiency of digital transformation, as well as the benefits provided to the community. The method used was Qualitative descriptive, encompassing data collection techniques such as interviews, observations, and documentation. Furthermore, the transformation of digital bureaucratic services through the SALAMAN Application was conducted effectively and efficiently, providing benefits to the community and the Bandung City Population and Civil Registration Office. These benefits encompassed convenient and streamlined access to administrative services for the community, as well as enhanced effectiveness, efficiency, and productivity of service delivery.